2019
DOI: 10.1111/cea.13319
|View full text |Cite
|
Sign up to set email alerts
|

Individual risk assessment tool for school‐age asthma prediction in UK birth cohort

Abstract: Summary Background Current published asthma predictive tools have moderate positive likelihood ratios (+LR) but high negative likelihood ratios (−LR) based on their recommended cut‐offs, which limit their clinical usefulness. Objective To develop a simple clinically applicable asthma prediction tool within a population‐based birth cohort. Method Children from the Manchester Asthma and Allergy Study (MAAS) attended follow‐up at ages 3, 8 and 11 years. Data on preschool wheeze were extracted from primary‐care re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Of the 21 models carried forward for qualitative analysis (Table ), six were developed in the general population 24,31,36‐38 and 15 within high‐risk populations, the latter restricting inclusion to children with a parental history of allergy/asthma (four models) 25,28‐29,39 or asthma‐like symptoms (11 models, 30,40 with nine specifically targeting children experiencing wheeze 26‐27,41‐47 ). Only one model was derived based on predictors initially associated with childhood asthma within a low‐income, Puerto Rican population 37 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 21 models carried forward for qualitative analysis (Table ), six were developed in the general population 24,31,36‐38 and 15 within high‐risk populations, the latter restricting inclusion to children with a parental history of allergy/asthma (four models) 25,28‐29,39 or asthma‐like symptoms (11 models, 30,40 with nine specifically targeting children experiencing wheeze 26‐27,41‐47 ). Only one model was derived based on predictors initially associated with childhood asthma within a low‐income, Puerto Rican population 37 …”
Section: Resultsmentioning
confidence: 99%
“…Upon critical appraisal, at least eight studies were identified as lacking sufficient power to develop stable prediction models; these studies had a ratio of candidate predictors to total number of cases lower than recommended (at least 20 cases per candidate predictor) to achieve sufficient power 30,38,41‐42,44‐45,47 . Underpowered studies risk important predictors not being selected (under‐fitting—Type II error), the incorrect selection of predictors (overfitting—Type I error) as well as the misrepresentation of the associated directionality between predictors and the outcome 59…”
Section: Discussionmentioning
confidence: 99%
“…1 They used a data-driven methodology to derive exacerbation trajectories in the Manchester Asthma and Allergy Study cohort. 2 Amongst the 160 participants with at least one severe exacerbation, they found two clusters: "Infrequent exacerbations" (93.7%) and "Early-onset frequent exacerbations" (6.3%) ( Figure 1). Limited breastfeeding was associated with the more severe phenotype.…”
Section: Severe Wheeze Aspergillus and A New Approach For Anaphylaxismentioning
confidence: 98%
“…In this issue of the Journal, Deliu et al look at the longitudinal trajectories of medical record confirmed severe exacerbations of wheeze from infancy into childhood . They used a data‐driven methodology to derive exacerbation trajectories in the Manchester Asthma and Allergy Study cohort . Amongst the 160 participants with at least one severe exacerbation, they found two clusters: “Infrequent exacerbations” (93.7%) and “Early‐onset frequent exacerbations” (6.3%) (Figure ).…”
mentioning
confidence: 99%
“…These variables were chosen on the basis of differences seen in the demographic data and previous knowledge from the cohort. 45,46 As not to over-t the models, we chose to merge the maternal and paternal variables on atopy and asthma into one parental variable each. We did not correct for pet ownership separately or as a merged variable, as only cat-ownership was signi cantly different, and as not to over-t the models.…”
Section: Statistical Analysesmentioning
confidence: 99%